2022
DOI: 10.18844/cjes.v17i3.7004
|View full text |Cite
|
Sign up to set email alerts
|

Developing the research potential of a social teacher in the context of digital technologies

Abstract: In the system of modern domestic education, the problem of professional-pedagogical activity of teachers is one of the most popular and relevant, deserving separate empirical research and further practical study. This article aims to consider the role of a social teacher in society and reviews the research potential of a social teacher. Opportunities such as advanced training courses in research capacity development, ICT courses, speech at scientific conferences, participation in professional competitions, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…By following these approaches, young researchers will have the support they need to achieve great success. (McIntyre & Cameron, 2011;Ambler, Harvey, & Cahir, 2016;Rysbek et al, 2022) III) The results of using the university's PLC to develop young researchers were tested and it was found that there were 21 proposed research projects. The evaluation scores were in the range of 3.67 to 4.08, passing the evaluation standard of 3.51 (Chamnan, 2019) which is 100 percent.…”
Section: Discussionmentioning
confidence: 99%
“…By following these approaches, young researchers will have the support they need to achieve great success. (McIntyre & Cameron, 2011;Ambler, Harvey, & Cahir, 2016;Rysbek et al, 2022) III) The results of using the university's PLC to develop young researchers were tested and it was found that there were 21 proposed research projects. The evaluation scores were in the range of 3.67 to 4.08, passing the evaluation standard of 3.51 (Chamnan, 2019) which is 100 percent.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, with all the initial semantic similarities, the concepts of "personal potential of a teacher" and "pedagogical potential" cannot be considered identical (Geng, Chai, Jong, & Luk, 2021;Rysbek et al, 2022;Vykhrushch, Romanyshyna, Pehota, Shorobura, & Kravets, 2020;Yorgancıoğlu, Tunalı, & Çetinel, 2022). If the personal potential of a teacher remains a psychological construct, then the concept of "pedagogical potential" is considered mainly from scientific and pedagogical positions (Tan, Rajendran, Muslim, Alias, & Yusof, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is the primary duty of teacher training universities and teacher training programmes to evaluate the basic knowledge, skills and competencies of teacher candidates on computer technologies and their use, to develop policies to improve them and educate them about their inadequacies (Flowers & Algozzine, 2000;Rysbek et al, 2022). The application of information and communication technologies in primary schools is seen as a modern necessity.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%